Analisis Pengaruh Kecepatan Putaran Spindel Terhadap Kekasaran Permukaan Benda Kerja Pada Proses Pengerjaan Mesin Bubut - F. Pambudi; H. Abdillah; W. Andriyanto (Dinamika Teknik Mesin, 2022)
The purpose of this research was to obtain result fromthe effect off  the influence of spindle rotation speedon the roughness of the workpiece using rugotest byknowing the different roughness treatmen of each rpmspecimens. This research uses an experimentalmethod, workpieces with the type of steel material  ST.37  made 10 specimens in the from of 2 workpieces. Each workpiece contains 5 specimens tobe analyzed using the rugotest tool at differentvariations of spindel rotation speed. Variations  ofspindle rotation speed are 693 rpm, 501 rpm, 252 rpm, 125 rpm, 63 rpm. Turned using the same tooland the same feeding speed on one variable. After theworkpiece is turned it is then analyzed to get theroughness value of the workpiece. Data analysis usingrugotest by knowing the standard value of roughnesson the rugotest. This study obtains data results thatshow the faster the spindle rotation on the lathe, thelower the workpiece roughness value on the rugotest.